Exercises to improve the position of the head in tennis strokes - Fernández López, M. (Coaching and Sport Science Review, 2020)
Tennis is an opposition sport in which we hit the ball with the racket whilst in movement, attempting to place it as far away from our opponent as possible but within the court. It is also a high-speed interception sport, and the speed increases with the level of the players. This article presents different specific on-court exercises to help players to improve their capacity to adapt to changing tennis dynamics.